Transcending Traditional Treatment: The Therapeutical Potential of Nanovesicles for Transdermal Baclofen Delivery in Repeated Traumatic Brain Injury - Nermin M. Sheta; Amira A. El-Gazar; Ghada M. Ragab; Marwa A. Essa; Khaled M. Abdel-Haleem; Rania Moataz El-Dahmy (Advanced Pharmaceutical Bulletin)
Purpose: The repositioning of previously approved drugs is occupying the researchers’ plans. Baclofen (Bac) was our candidate for its established neuroprotective capacity, with a proposal of efficient drug delivery as non-ionic surfactant-based nanovesicles (NISNV) formulae against mild repetitive traumatic brain injury (mRTBI) in rats, thus reducing the number of orally or injected medications, especially in severely comatose patients or pediatrics. Methods: A (23 ) factorial design was implemented for confining Bac-loaded NISNV formulae, where a bunch of variables were inspected. An in-vivo experiment was done to test the prepared formula’s efficacy transdermally. The following parameters were measured: brain expression of gamma amino butyric acid B (GABAB), protein kinase C- α (PKC-α), focal adhesion kinase (FAK), TNF-α and nuclear factor kappa B (NF-κB) p65, malondialdehyde (MDA), superoxide dismutase (SOD), and histopathology. Results: The particle size (PS) and entrapment efficiency percent (EE%) speckled from 60.40±0.28% to 88.02±0.01% for the former and 174.64±0.93 to 1174.50±3.54 nm for the latter. In vitro release% after 8 hours ranged from 63.25±5.47% to 84.79±3.75%. The optimized formula (F4) illustrated desirability=1, with 630.09±3.53 µg/cm2 of Bac permeated over 8 hours, which equates to 100% of Bac. Bac post-trauma treatment restored brain expression of GABAB and PKC-α, while decreasing FAK. Besides enhancing the histological findings, the anti-inflammatory effect was clear by decreasing TNF-α and NF-κB p65. Consequently, significant antioxidant sequelae were revealed herein by diminishing MDA levels and restoring SOD activity. Conclusion: Transdermal delivery of Bac-loaded niosomes confirmed neuroprotection and succeeded in surpassing skin-to-brain barriers, which makes it a promising therapeutic option for repeated traumas.